DRIS II: Interpretation of DRIS indices in oil palm cultivation - Herrera-Peña, Gustavo Enrique; Dussán-Sarria, Saúl; Camacho-Tamayo, Jesús Hernán (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
The nutritional diagnosis based on leaf tissue analysis is an efficient tool for detecting nutritional imbalances and assisting the fertilizer recommendation process. Therefore, the objective was to use the indices obtained through the Integrated Diagnosis and Recommendation System (DRIS) in oil palm cultivation to interpret them based on the criteria of excess limitation (LE), deficiency limitation (LF), and non-limiting (NL). It was found that sulfur, potassium, and magnesium are not presenting any limitations for production, while zinc, iron, and copper showed deficiency limitations, and nitrogen an excess limitation. The likelihood of a reaction to an augmented nutrient supply via fertilizers was assessed. The results revealed a strong likelihood of a negative response for nitrogen, while elements like phosphorus, potassium, calcium, magnesium, sulfur, zinc, and boron exhibited no significant response. As a final implemented methodology, critical levels and sufficiency ranges were calculated for each element, based on the correlation between the nutrient quantity in leaf tissue and the DRIS index obtained for each element in everyone. Differences were found compared to what has been reported by other authors.